1998
DOI: 10.1038/bjc.1998.221
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 20 mRNA in peripheral venous blood of colorectal carcinoma patients

Abstract: Summary A highly sensitive system was previously developed by us to detect the presence of colorectal carcinoma cells in blood in the form of cytokeratin 20 (CK20) mRNA. In the present study, we used an improved version of this system to analyse the peripheral blood of 28 patients with colorectal carcinoma, five patients with non-cancerous intestinal diseases and six normal controls for the presence or absence of CK20 mRNA and to investigate the relationship between the mRNA results and prognosis. All eight pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 14 publications
0
35
0
1
Order By: Relevance
“…In the originally investigated stabilized lysates from bone marrow of CID patients (n = 14) and peripheral blood of HD (n = 33) we had encountered positive results in 35% and 24% respectively. This represents a markedly lower diagnostic specificity than has been previously reported for CK20 detection by RT-PCR (Burchill et al, 1995;Soeth et al, 1997;Funaki et al, 1998). To verify these results we investigated the interference of mRNA from nucleated blood cells on the CK20 RT-PCR specificity in a panel of peripheral blood samples from ICU patients with non-malignant conditions (Table 1).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In the originally investigated stabilized lysates from bone marrow of CID patients (n = 14) and peripheral blood of HD (n = 33) we had encountered positive results in 35% and 24% respectively. This represents a markedly lower diagnostic specificity than has been previously reported for CK20 detection by RT-PCR (Burchill et al, 1995;Soeth et al, 1997;Funaki et al, 1998). To verify these results we investigated the interference of mRNA from nucleated blood cells on the CK20 RT-PCR specificity in a panel of peripheral blood samples from ICU patients with non-malignant conditions (Table 1).…”
Section: Resultsmentioning
confidence: 93%
“…In a number of clinical CK20 RT-PCR studies, comparable diagnostic specificities have been achieved for conventional (Burchill et al, 1995), nested RT-PCR (Soeth et al, 1996) and even double-nested RT-PCR (Funaki et al, 1998) systems. Recent studies have assigned clinical significance and prognostic value to the detection of CK20 mRNA-positive cells in bone marrow and peripheral blood samples of breast, gastric, pancreatic and colorectal cancer patients (Soeth et al, 1996(Soeth et al, , 1997Bostick et al, 1998;Weitz et al, 1998).…”
mentioning
confidence: 99%
“…Eight studies were excluded as they reported only on preoperative blood sampling (Bessa et al, 2001;Fujita et al, 2001;Wong et al, 2001;Zhang et al, 2005;Douard et al, 2006;Iinuma et al, 2006;Wang et al, 2006;Friederichs et al, 2007). Nine studies were excluded as they contained data from which outcomes could not be extracted, of which four were excluded as they combined positive results of molecular detection of multiple samples and their effect on prognosis (Hardingham et al, 2000;Guller et al, 2002;Bosch et al, 2003;Koyanagi et al, 2008), and five were excluded as it was impossible to extract the data for outcomes of interest (White and Griffiths, 1976;Funaki et al, 1998;Wyld et al, 1998;Conzelmann et al, 2005;Wang et al, 2007). Five studies were excluded as they were reviews or systematic reviews, which did not report on prognostic outcomes (Tsavellas et al, 2001;Sleijfer et al, 2007;Riethdorf et al, 2008;Sergeant et al, 2008;Tsouma et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Funaki et al (1998) detected CK20 mRNA in the peripheral blood of advanced colorectal carcinoma patients, which seems to present an indicator of possible recurrence in individual patients. It has been suggested that CK20 mRNA detection by RT-PCR in the peripheral blood and bone marrow is a promising marker for circulating tumor cells of epithelial origin Johnson et al, 1995;Soeth et al, 1997;Katsumata et al, 2006).…”
Section: Discussionmentioning
confidence: 99%